ISOLASI, IDENTIFIKASI DAN UJI SENSITIVITAS ANTIBIOTIK TERHADAP PASTEURELLA MULTOCIDA ASAL SAPI YANG DIPOTONG DI RUMAH PEMOTONGAN HEWAN OEBA KUPANG - Harrold Subu Taopan; Maxs U.E. Sanam; Elisabet Tangkonda (Jurnal Veteriner Nusantara, 2016)
Pasteurella multocida is a Gram-negative bacteria which are not able to grow on media MacConkey agar, cocobacill shaped, are facultative anaerobic and non-motile with the biochemical characteristics that have catalase and oxidase activity and ferment glucose but not ferment lactose. P. multocida is a normal flora in the respiratory tract of cattle. There are two serotypes of P. Multocida which cause disease in cattle that are serotype A causes Shippin fever and serotype B:2 causes septicaemia epizootica (SE). This study aimed to isolate and identify the P. multocida in cattle slaughte houses Oeba Kupang and to determine the level of sensitivity to multiple antibiotics. As much as 30 samples of tracheal swabs Bali cattle slaughtered in slaughter houses Oeba Kupang taken as samples. Samples are then isolated in media blood agar. Separate colonies were taken and stained with Gram stain and then cultured on MacConkey agar. Colonies tested with biochemical tests consisting of carbohydrate fermentation tests on triple sugar iron agar (TSIA), motility test on sulphite indole motility (SIM), catalase test on nutrient broth (NB) and the oxidase test on oxidase strip. The sensitivity of P. multocida were tested by inhibition zone to the antibiotic ampicillin, amoxicillin, sefoksitin, tetracycline and ciprofloxacin in the Muller Hinton Agar media (MHA). The results showed that P. multocida was isolated from one tracheal swab samples. This P. multocida isolates were sensitive to ciprofloxacin, while are resistant to ampicillin, amoxicillin, tetracycline and cefoxitin.